A smart secure healthcare monitoring system with Internet of Medical Things. (July 2022) - Shreya, Shashi; Chatterjee, Kakali; Singh, Ashish
Abstract: The new era of information technologies made smart healthcare by including edge, Internet of Things (loT), Internet of Medical Things (IoMT), cloud computing etc. This adaptation has partially replaced the old medical system, making healthcare more efficient, easy, and customized. Wireless medical sensors are used in the smart healthcare sector to capture the patient's health data and transmit it to the remote server for treatment or diagnostic purposes. Every time a cloud-based solution is adopted to collect and preserve the sensitive and personal health information. This collected patient data is shared between the different stakeholders across the network. Due to this, healthcare systems are vulnerable to confidentiality, integrity and privacy threats. Secure data access is a big challenge in such systems. In this paper, a lightweight authentication technique with the privacy-preserving schema using fully homomorphic encryption is proposed. This approach can be used for a secure access of patient data through online mode, and also the data can be shared in an encrypted format for desired purposes of stakeholders. The proposed authentication scheme is for Internet of Medical Things that can resist all network attacks and is easy to implement. The performance analysis of the proposed work shows that overall execution time (80.03%), communication cost (15.62%) and energy consumption (79.19%) is reduced in comparison with existing work. Graphical abstract: Highlights: A lightweight mutual authentication scheme for smart healthcare systems is designed and implemented using on login ID, password, and perceptual hash based biometric security. A formal security analysis is introduced using Burrows–Abadi–Needham (BAN) logic that resists all well-known attacks and provide anonymity of patient identity. A performance comparison of the proposed scheme with existing schemes is also carried out in terms of security features and communication overheads, computation overheads, storage and network throughput.